Unraveling the connection: Digital competence and steam readiness in biology pre-service teachers - Aidil Adhani (Biosfer: Jurnal Pendidikan Biologi, 2023)
Digital competence is one of the things that pre-service teachers need to have in order to survive in global competition. The goal of this reasearch is to know the correlation between digital competence of biology pre-service teachers and their readiness to apply STEAM-oriented learning. This research is a bivariate correlational quantitative research. The sampling technique used in this study is the quota sampling technique with number of sample are 90 students. The instrument used in this study was a questionnaire to measure students' digital competency skills and their readiness for STEAM. The data analysis technique in this study is inferential statistical analysis in the form of a bivariate correlation test (Spearman Rank correlation). The Correlation Coefficient value shows a coefficient of 0.622, meaning there is a strong relationship between digital competence and readiness for STEAM. The digital competence of pre-service teachers is considered necessary in STEAM-oriented learning because technology and digital tools play an essential role in improving the quality of learning and enabling more interactive, innovative, and fun learning experiences.